2023
DOI: 10.1002/nml.21555
|View full text |Cite
|
Sign up to set email alerts
|

A study on corporate foundation and philanthropy: Does governance matter for organizational performance?

Abstract: Given the increased social and strategic value of corporate philanthropy (CP) in businesses, a growing number of corporations have established associated corporate foundations to institutionalize and formalize their CP. Notably, CP has been channeled through team charitable foundations in professional sport, which are corporate foundations closely tied to their parent teams while having own (quasi) independent governance structure. However, these corporate foundations have received less scholarly attention. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Previous studies confirmed a positive relationship between the presence of distinct practices and higher levels of organizational effectiveness (Forbes 1998;Herman andRenz 2000, 2004;Renz and Herman 2016). However, earlier studies have mostly focused on the individual drivers of organizational effectiveness, such as governance issues, including the effect of board structural characteristics and board leadership (Yang and Babiak 2023), board involvement (Minciullo and Pedrini 2020), and knowledge-transfer methods (Minciullo andPedrini 2014, 2015). Other drivers concern general organizational characteristics and practices, such as "organizational climate, organizational structure, and the presence of unionism" (Forbes 1998, p. 190) or successful stakeholder management, through which organizations are perceived to be more effective (Balser and McClusky 2005).…”
Section: Antecedents Of Organizational Effectivenessmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies confirmed a positive relationship between the presence of distinct practices and higher levels of organizational effectiveness (Forbes 1998;Herman andRenz 2000, 2004;Renz and Herman 2016). However, earlier studies have mostly focused on the individual drivers of organizational effectiveness, such as governance issues, including the effect of board structural characteristics and board leadership (Yang and Babiak 2023), board involvement (Minciullo and Pedrini 2020), and knowledge-transfer methods (Minciullo andPedrini 2014, 2015). Other drivers concern general organizational characteristics and practices, such as "organizational climate, organizational structure, and the presence of unionism" (Forbes 1998, p. 190) or successful stakeholder management, through which organizations are perceived to be more effective (Balser and McClusky 2005).…”
Section: Antecedents Of Organizational Effectivenessmentioning
confidence: 89%
“…Additionally, to prove their effectiveness, they must focus primarily on monitoring and evaluating activities. One way to interpret this result is to remember the increasing pressure on foundations for professional impact measurements to show what the foundation has achieved, for which pure output calculations or storytelling reports are no longer sufficient (Balser and McClusky 2005;Lecy et al 2012;Minciullo and Pedrini 2014;Yang and Babiak 2023). Instead, comprehensive assessments of the intended positive and unintended negative effects on immediate stakeholders and the organizational environment are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations